Protocol for transcriptomic and epigenomic analyses of tip-like endothelial cells using scRNA-seq and ChIP-seq - Shintaro Funasaki; Yuri Miyamura; Shunsuke Kamei; Akhinur Rahman; Masaya Yamazaki; Shingo Usuki; Keiichiro Yasunaga; Yorifumi Satou; Hiroto Ohguchi; Takashi Minami (STAR Protocols)
Summary: Angiogenesis begins as endothelial cells migrate, forming a sprouting tip and subsequent growth-rich stalk cells. Here, we present a protocol for transcriptomic and epigenomic analyses of tip-like cells in cultured endothelial cells. We describe steps for stimulating human umbilical vein endothelial cells (HUVECs) with vascular endothelial cell growth factor (VEGF) to generate tip-like cells. We then detail procedures for library preparation for single-cell RNA sequencing (RNA-seq) and chromatin immunoprecipitation sequencing (ChIP-seq), and data analysis. This scalable protocol is also applicable to diverse omics studies, including proteomics and metabolomics.For complete details on the use and execution of this protocol, please refer to Miyamura et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.